EFEKTIVITAS EKSTRAKURIKULER PRAMUKA SMAN 1 PONTANG KABUPATEN SERANG DI MASA PANDEMI - Rilva Deni Yogatama; Asmunah; Surya Adam Hilmi; Muhammad Anggie Farizqi Prasadana (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
Pramuka or Praja Muda Karana is a scouting organization in Indonesia. Pramuka is one of the extracurricular activities at SMAN 1 Pontang. This study aims to determine the level of effectiveness of Pramuka extracurricular activities during the pandemic in terms of achieving the goals that have been set both in the work program and national consensus. This study took place at SMAN 1 Pontang where data collection used interviews and observations and compared the data obtained with the relevant literature, the data that had been collected was analyzed by inductive analysis and validated by data triangulation. This research is also intended to measure the effectiveness of Pramuka extracurricular management at SMAN 1 Pontang in carrying out various programs during the pandemic. The research results show that the pandemic has affected many aspects of life. The implementation of extracurricular activities at SMAN 1 Pontang was also affected. Nevertheless, Pramuka extracurricular activities at SMAN 1 Pontang are still going well. The activities are carried out online through the Zoom Meeting application. After the pandemic subsided, Pramuka was held offline again.